STUDI ANALISIS FATWA TARJIH MUHAMMADIYAH TENTANG ROKOK DAN DAMPAKNYA TERHADAP COVID-19 - Mohamad Ilyas Abas; Salahudin Pakaya; Syahrial Syahrial (Gapenas Publisher, 2022)
In essence, according to the fatwa and Islamic views that cigarettes are included in the haram category. Some views say that smoking is makruh and even permissible. But the strongest opinion is that smoking is forbidden in Islam, especially in the fatwa tarjih Muhammadiyah which strictly forbids smoking because smoking is an act that can harm oneself and others. In this study, the researcher wanted to analyze the study on the compliance of tarjih prohibition of smoking in Muhammadiyah environment to student organizations in Muhammadiyah. This research uses quantitative methods, the quantitative method was chosen because it is an approach whose specifications are systematic, planned and clearly structured from the beginning to the making of the research design. The purpose of this study was to obtain an analysis study of the compliance of Muhammadiyah members with Muhammadiyah tarjih on cigarettes. The results of the study will display statistics on the compliance of Muhammadiyah members as well as statistics on Muhammadiyah members who still smoke so that it is contrary to the tarjih and smoking laws in Islam, which are haram. The benefit of this study is that it can display data in clusters of smokers who are in the Muhammadiyah environment. The results of the study indicate that in fact, according to knowledge, everyone agrees that cigarettes are haram and adherence to tarjih is indeed quite high, but it is not accompanied by obedience to leave the smoking habit.